2008
DOI: 10.1002/qsar.200730082
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of Vasopressin V2 Receptor Tetramer in Hydrated Lipid Membrane

Abstract: Based on accessible experimental data we have constructed a model of Vasopressin V2 Receptor (V2R) tetramer in fully hydrated lipid membrane. To the best of our knowledge, this is the first Molecular Dynamics (MD) simulation of the tetramer model of a GPCR other than rhodopsin. The model consists of three inactive and one active V2R monomers. The activated unit is stabilized by Gsa (Ile 382 -Leu 394 ) fragment and includes its natural ligand -vasopressin (AVP) docked. The pairs of neighboring protomers form co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 125 publications
2
5
0
Order By: Relevance
“…The V2R 3D model was allowed to relax for up to 50 ns of MD simulations and from the structural point of view (RMSD) stability is reached at about 20 ns (Figure a). Previously, similar RMSD values were observed in an MD study of the V2R tetramer embedded in hydrated lipid membrane, where helices of the V2R monomers showed RMSD values between 2.5 and 4.5 Å in a short time simulation …”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The V2R 3D model was allowed to relax for up to 50 ns of MD simulations and from the structural point of view (RMSD) stability is reached at about 20 ns (Figure a). Previously, similar RMSD values were observed in an MD study of the V2R tetramer embedded in hydrated lipid membrane, where helices of the V2R monomers showed RMSD values between 2.5 and 4.5 Å in a short time simulation …”
Section: Resultssupporting
confidence: 63%
“…Previously, similar RMSD values were observed in an MD study of the V2R tetramer embedded in hydrated lipid membrane, where helices of the V2R monomers showed RMSD values between 2.5 and 4.5 Å in a short time simulation. [52] According to V2R RMSF values (Figure 2b), the Nterminus and third intracellular loop show fluctuations up to 5 Å, as well as in the connecting loops of the receptor; these fluctuations have been also reported for other GPCRs [17,53] and considered important for ligand binding and signal transduction. [54] It has been shown that the second and third intracellular loops are involved in G-protein activation in many GPCRs.…”
Section: Results and Discussion 31 | Structural Analysissupporting
confidence: 55%
“…Such methods have also been used to study of GPCR dimerization and oligomerization (Fanelli et al, 2013;Jonas et al, 2015;Altwaijri et al, 2017). Examples include the study of rhodopsin dimer (Filizola et al, 2006) and simulations of vasopressin receptor oligomerization (Witt et al, 2008) and of the mGluR 2 -5-HT 2A heterodimeric complex (Bruno et al, 2009). A structural characterization of the human A 2A adenosine receptor homodimer was very recently provided (Altwaijri et al, 2017) using a new coarse-grained approach to molecular dynamics simulations, specifically developed for identifying helix-helix interactions in GPCR.…”
Section: Interaction Interfacesmentioning
confidence: 99%
“…Moreover, a 40-ns MD simulation was performed on the heterodimeric complex of the mGluR 2 and 5-HT 2A receptors, which was also assembled around the TM4/5 interface [ 139 ]. Relying on an interface proposed by Schultz et al [ 140 ] for the vasopressin receptor V2R dimer, a V 2 R tetramer was studied by a 5-ns all-atom MD simulation, which indicated that TM3/4–TM6/7 interface relates to the transactivation between active and inactive monomers [ 141 ]. Furthermore, MD simulations were performed on four different MOR–DOR heterodimers and from that TM1/7 and TM4/5 were identified as the most likely interfaces [ 142 ].…”
Section: Bn-pagementioning
confidence: 99%